Peran Pemerintah Nagari dalam Pembangunan Fisik di Nagari Tanjung Barulak, Kecamatan Batipuh, Kabupaten Tanah Datar - Fikra Ridhatul Hasanah; Sinta Westika Putri (YASIN, 2026)
Physical development at the nagari level is the spearhead of regional development in West Sumatra, but the role of the nagari government in this process has its own distinctiveness because it cannot be separated from the customary system that is strongly rooted in community life. This study aims to examine the role of the Tanjung Barulak Nagari Government in physical development and to identify the factors that influence it. This study employed a descriptive qualitative approach involving 21 informants selected purposively, including nagari officials, jorong heads, representatives of BPRN, KAN, and the community. Data were collected through in-depth interviews and documentation studies, and were then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the Tanjung Barulak Nagari Government had carried out five roles according to Siagian, namely stabilizer, innovator, modernizer, pioneer, and implementer, which were manifested through tiered deliberation, innovation in budget and irrigation management, the implementation of RPJM, budget transparency, and a self-management system based on TPK. The most dominant roles were those of stabilizer and implementer, while the roles of innovator, modernizer, and pioneer still need to be strengthened, especially in the use of technology and in increasing public awareness of maintaining development outcomes. Development implementation was supported by the synergy of tungku tigo sajarangan, the spirit of gotong royong, and the technical support of the regency government, but was hindered by delays in fund disbursement, customary land constraints, low awareness of infrastructure maintenance, and the central government’s budget efficiency policy. These findings affirm that strengthening the role of the nagari government in physical development requires more adaptive strategies through optimizing alternative funding schemes and integrating customary values into nagari development policies. Keywords: Role of the Nagari Government; Physical Development; Local Governance; Infrastructure; Customary-Based Development